Analisis Pengaruh Orientasi Kewirausahaan Dan Orientasi Pasar Terhadap Keunggulan Bersaing Melalui Inovasi Produk Olahan Susu Sapi Di Kecamatan Cipayung - Wulandary, Putri Rahma; Widyastuti, Sri; Rachbini , Widarto (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
The purpose of this study was to determine the effect of the influence of entrepreneurial orientation and market orientation on competitive advantage through innovation in processed cow's milk products in Cipayung District. The sampling technique is total sampling, namely a sample that represents the total population. Data collection uses a questionnaire. Technical data analysis uses Structural Equation Modeling (SEM) analysis which is processed with SmartPLS software. The results of this research prove that the variables entrepreneurial orientation and market orientation have a significant effect on product innovation. The market orientation variable does not have a significant effect on competitive advantage, while the market orientation variable and product innovation variable have a significant effect on competitive advantage. The research results also show that the most dominant direct influence is the direct influence between entrepreneurial.